2019
DOI: 10.1002/ejoc.201900569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluations of “1,4‐Triazolyl Combretacoumarins” and Desmethoxy Analogs

Abstract: 1,4‐Triazolyl combretacoumarins have been prepared by linking the trimethoxyarene unit of combretastatin A4 with coumarins, via a 1,2,3‐triazole. For this, 4‐azidocoumarins were accessed by a sequential two‐step, one‐pot reaction of 4‐hydroxycoumarins with (benzotriazol‐1‐yloxy)tris(dimethylamino)phosphonium hexafluorophosphate (BOP), followed by reaction with NaN3. In the reaction with BOP, a coumarin‐derived phosphonium ion intermediate seems to form, leading to an O4‐(benzotriazolyl)coumarin derivative. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Six 4-azidocoumarin precursors 2 a-f were synthesized from their corresponding 4-hydroxylcoumarins 1 a-f [24,25,26] by following literature procedure. [27] On the other hand, silyl protected O-alkynylated nucleoside precursors 5 a and 5 b were synthesized in two steps starting with the selective protection of C-5'-primary hydroxy group of 2'-deoxyuridine (3 a) and thymidine (3 b) with TBDPSCl in pyridine followed by propargylation of 3'-hydroxyl group of the resulted silylated nucleosides 4 a and 4 b with propargyl bromide and sodium hydride as a base in THF at 0 °C in an overall yields of 85 % and 80 %, respectively. [28] Now, the synthesized azido-and alkynyl-derivatives were used for click chemistry reaction to obtain the coumarin-triazolylmethyl nucleoside conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Six 4-azidocoumarin precursors 2 a-f were synthesized from their corresponding 4-hydroxylcoumarins 1 a-f [24,25,26] by following literature procedure. [27] On the other hand, silyl protected O-alkynylated nucleoside precursors 5 a and 5 b were synthesized in two steps starting with the selective protection of C-5'-primary hydroxy group of 2'-deoxyuridine (3 a) and thymidine (3 b) with TBDPSCl in pyridine followed by propargylation of 3'-hydroxyl group of the resulted silylated nucleosides 4 a and 4 b with propargyl bromide and sodium hydride as a base in THF at 0 °C in an overall yields of 85 % and 80 %, respectively. [28] Now, the synthesized azido-and alkynyl-derivatives were used for click chemistry reaction to obtain the coumarin-triazolylmethyl nucleoside conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…As another demonstration of how the results from nucleoside modification chemistry translates to other areas, we developed a novel class of combretacoumarins, for antiproliferation evaluations [88] . The idea was to combine the biologically important A ring of combretastatin A4 with the physiologically important coumarins.…”
Section: Observations From Nucleoside Modification Chemistry Leading ...mentioning
confidence: 99%
“…74 µM, MTT assay) showed moderate activity against CEM cells [39,40] ; replacement of coumarin by flavonoid resulted in absence of activity as evidenced by that 1,2,3-triazole-flavonoid hybrids 14…”
Section: 23-triazole-carbohydrate Hybridsmentioning
confidence: 99%
“…The antiproliferative SAR of 1,2,3‐triazole‐coumarin hybrids 11 (IC 50 : 7.5–>100 µM, MTT assay) against K562 cells revealed that methoxy group at the para ‐position of coumarin moiety was critical for the activity, and movement of this substituent to meta ‐ or ortho ‐position led to significant loss of activity [ 38 ] ; the carbon spacer between 1,2,3‐triazole and coumarin may have some influence on the activity, and hybrids 12 (IC 50 : 58 µM, MTT assay) and 13 (IC 50 : 74 µM, MTT assay) showed moderate activity against CEM cells [ 39,40 ] ; replacement of coumarin by flavonoid resulted in absence of activity as evidenced by that 1,2,3‐triazole‐flavonoid hybrids 14 (IC 50 : >40 µM, MTT assay) were devoid of activity against HL‐60 cells. [ 41 ] Among them, hybrids 11a–c (IC 50 : 7.5–9.8 µM) were found to be most active against K562 cells and exhibited reactive oxygen species (ROS) production levels similar to that of esculetin.…”
Section: 23‐triazole‐tetrahydroisoquinoline/coumarin/flavonoid Hybridsmentioning
confidence: 99%